Learning Strategies for Improving Number Recognition Ability through Digital Stories - Khotimah, Laili Khusnul; Katoningsih, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Introduction to numbers in adank Early childhood varies, especially when it comes to recognizing numbers, one of which is by using digital stories. Seeing increasingly sophisticated technological developments in learning, children are also introduced to technology. This research aims to determine learning strategies for improving number recognition skills through digital stories. The subjects of this research were teachers, school principals, and children aged 4-5 years. The object of this research is number recognition. The data collection technique is through observation, namely collecting initial data related to the ability to recognize numbers, interviews are used to collect data related to learning strategies to improve the ability to recognize numbers through digital stories and documentation is used as supporting data in the ability to recognize numbers in early childhood. The data analysis technique used is data reduction, namely analyzing the data, grouping the data according to the data obtained, and then presenting the data, namely the data that has been reduced related to the ability to recognize numbers displayed according to the grouping. After presenting the data, then conclusions are drawn on the results of the research. The results of this research show that recognizing numbers using digital stories can improve concentration abilities and can also improve children's number recognition.